Assessing a behavioral nudge on healthcare leaders' intentions to implement evidence-based practices. - Maia Crawford; A James O'Malley; Ellen Meara; Taressa K Fraze; Amber E Barnato (PLoS ONE)
Importance Leaders of healthcare organizations play a key role in developing, prioritizing, and implementing plans to adopt new evidence-based practices. This study examined whether a letter with peer comparison data and social norms messaging impacted healthcare leaders' decision to access a website with resources to support evidence-based practice adoption. Methods Pragmatic, parallel-group, randomized controlled trial completed from December 2019 -June 2020. We randomized 2,387 healthcare leaders from health systems, hospitals, and physician practices in the United States, who had previously responded to our national survey of healthcare organizations, in a 1:1 allocation ratio to receive one of two cover letter versions via postal mail (all) and email (for the 60.6% with an email address), accompanying a report with their survey results. The "nudge" letter included messaging that highlighted how an organization's results compared to peers using text, color, and icons. Both nudge and control letters included links to a resource website. We interviewed 14 participants to understand how the letter and report impacted behaviors. Results Twenty-two of 1,194 leaders (1.8%) sent the nudge letter accessed online resources, compared to 17 of 1193 (1.4%) sent the control letter (p = 0.424). Nine of the 14 interviewed leaders stated that viewing the letter (regardless of version) and accompanying report influenced their decision to take a subsequent action other than accessing the website. Seven leaders forwarded the report or discussed the results with colleagues; two leaders stated that receiving the letter and report resulted in a concrete practice change. Conclusions Receiving cover letters with a behavioral nudge did not increase the likelihood that organizational leaders accessed a resource website. Qualitative results suggested that the survey report's peer comparison data may have been a motivator for prioritizing and delegating implementation activities, but leaders themselves did not access our online resources.